Bisphosphonate-Induced Osteonecrosis of the Maxilla Resembling a Persistent Endodontic Lesion - Mosaferi, Hossain; Fazlyab, Mahta; Sharifi, Sanaz; Rahimian, Sepideh (Iranian Endodontic Journal, 2016)
A 52-year-old Caucasian woman suffering from pain in the anterior maxillary region, presented to the clinic. Examination revealed a draining sinus tract in the buccal vestibule of the maxilla in the left anterior segment and expansion in the middle of palate. On conventional radiographic examination the lesion was initially assumed to be a periapical problem related to the incisors but subsequently it was diagnosed to be a bisphosphonate osteonecrosis. Conclusion: Acquiring a comprehensive medical history from the patients, conducting the clinical vitality tests and most importantly being familiar with the non-odontogenic lesions that can be side effects of specific medications are important requirements for reaching a correct diagnosis. Keywords: Bisphosphonate; Breast Cancer; Osteonecrosis; Periapical Pathosis